2005
DOI: 10.1158/1078-0432.ccr-05-0735
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Gene Expression and Prognosis in Breast Cancer Patients with 10 or More Positive Lymph Nodes

Abstract: Purpose:This study, along with two others, was done to develop the 21-gene Recurrence Score assay (Oncotype DX) that was validated in a subsequent independent study and is used to aid decision making about chemotherapy in estrogen receptor (ER)^positive, node-negative breast cancer patients. Experimental Design: Patients with z10 nodes diagnosed from 1979 to 1999 were identified. RNA was extracted from paraffin blocks, and expression of 203 candidate genes was quantified using reverse transcription-PCR (RT-PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
137
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(151 citation statements)
references
References 31 publications
8
137
1
1
Order By: Relevance
“…A lowered ASPP2 expression was linked to a poor clinical outcome in diffuse large B-cell lymphoma (Lossos et al, 2002) and with poor distant recurrence-free survival in breast cancer patients (Cobleigh et al, 2005). Reduced expression of ASPP2 has also been observed in a microarray study of metastatic breast cancer samples compared to nonmetastatic samples (Sgroi et al, 1999), suggesting that ASPP2 might be associated with breast cancer progression.…”
Section: Altered Aspp Expression In Human Cancers Is Linked To Tumourmentioning
confidence: 93%
“…A lowered ASPP2 expression was linked to a poor clinical outcome in diffuse large B-cell lymphoma (Lossos et al, 2002) and with poor distant recurrence-free survival in breast cancer patients (Cobleigh et al, 2005). Reduced expression of ASPP2 has also been observed in a microarray study of metastatic breast cancer samples compared to nonmetastatic samples (Sgroi et al, 1999), suggesting that ASPP2 might be associated with breast cancer progression.…”
Section: Altered Aspp Expression In Human Cancers Is Linked To Tumourmentioning
confidence: 93%
“…Reduction in DOI:http://dx.doi.org/10.7314/APJCP.2012.13.5.1727 Vitamin D Signaling andApoptosis Specific Regulator of p53 in Breast Cancer ASPP2 expression has been observed in microarray study of both invasive and metastatic breast cancer samples compared to normal breast samples, suggesting possible involvement of ASPP2 in breast cancer progression (Sgroi et al, 1999). Study carried out by Cobleigh et al (2005) demonstrated independent association of ASPP2/ TP53BP2 gene with distal recurrence in breast cancer patients. They have linked higher ASPP2 expression with longer distal recurrence free survival.…”
Section: Aspps: Task In Breast Cancermentioning
confidence: 94%
“…Several commercial molecular classifiers, based on multiplexed analyses of the RNAs of 21-70 gene products, have recently been introduced into the market in order to assist in therapy decisions making. [2][3][4] These purely RNA-based tests share the disadvantage that gradual changes of each parameter must be measured, and that these measurements are strongly dependent on tumor cell purity.…”
Section: Introductionmentioning
confidence: 99%